2016
DOI: 10.1093/hmg/ddw282
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the polyglutamylase geneTTLL5, expressed in photoreceptor cells and spermatozoa, are associated with cone-rod degeneration and reduced male fertility

Abstract: variants also displayed a substantial reduction in sperm motility and infertility, whereas those carrying missense changes were fertile. Defects in this polyglutamylase in humans have recently been associated with cone photoreceptor dystrophy, while mouse models carrying truncating mutations in the same gene also display reduced fertility in male animals. We examined the expression levels of TTLL5 in various human tissues and determined that this gene has multiple viable isoforms, being highly expressed in tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Alternatively, the absence of the deglutamylase CCP1 could have a stronger functional impact because this enzyme reverses the glutamylation generated by several polyglutamylases, each of them having a distinct function in photoreceptor cells. For example, the glutamylase TTLL5, which has been found mutated in human retinopathies (Bedoni et al, 2016), specifically modifies the X-linked protein RPGR. The massive degeneration of photoreceptors in the Ttll5 −/− mice was shown to result from the absence of glutamylation of RPGR rather than from aberrant tubulin glutamylation (Sun et al, 2016).…”
Section: Research Articlementioning
confidence: 99%
“…Alternatively, the absence of the deglutamylase CCP1 could have a stronger functional impact because this enzyme reverses the glutamylation generated by several polyglutamylases, each of them having a distinct function in photoreceptor cells. For example, the glutamylase TTLL5, which has been found mutated in human retinopathies (Bedoni et al, 2016), specifically modifies the X-linked protein RPGR. The massive degeneration of photoreceptors in the Ttll5 −/− mice was shown to result from the absence of glutamylation of RPGR rather than from aberrant tubulin glutamylation (Sun et al, 2016).…”
Section: Research Articlementioning
confidence: 99%
“…It is very unlikely that DmTTLL5 possesses such transcriptional cofactor activity, as the protein does not contain this additional C-terminal domain (Supplementary Figure 1 ). It was recently found that mutations in human TTLL5 are associated with retinal dystrophy 52 , 53 , and two recent studies have identified the gene encoding retinitis pigmentosa GTPase regulator (RPGR) as a specific physiological substrate of mammalian TTLL5 54 , 55 . RPGR is one of the genes commonly mutated in retinitis pigmentosa, as RPGR mutations account for around 20% of all retinitis pigmentosa cases 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Among PTMs, polyglutamylation of α- or β-tubulin tails occurs most abundantly on stable MT structures such as the ones found in ciliary axoneme and neurons 2 , 3 . Its dysregulation causes impaired mucous flow 4 , male infertility 5 , retinal degeneration 6 , 7 , and aberrant ciliary beating 8 . Mislocalization of tubulin glutamylase TTLL6 is found in Joubert syndrome 9 .…”
Section: Introductionmentioning
confidence: 99%